Differential innate immune response of endometrial cells to porcine reproductive and respiratory syndrome virus type 1 versus type 2. - Muttarin Lothong; Dran Rukarcheep; Suphot Wattanaphansak; Sumpun Thammacharoen; Chatsri Deachapunya; Sutthasinee Poonyachoti (PLoS ONE, 2023)
Modification of cellular and immunological events due to porcine reproductive and respiratory syndrome virus (PRRSV) infection is associated with pathogenesis in lungs. PRRSV also causes female reproductive dysfunction and persistent infection which can spread to fetus, stillbirth, and offspring. In this study, changes in cellular and innate immune responses to PRRSV type 1 or type 2 infection, including expression of PRRSV mediators, mRNA expression of Toll-like receptors (TLRs) and cytokine, and cytokine secretion, were examined in primary porcine glandular endometrial cells (PGE). Cell infectivity as observed by cytopathic effect (CPE), PRRSV nucleocapsid proteins, and viral nucleic acids was detected as early as two days post-infection (2 dpi) and persisted until 6 dpi. A higher percentage of CPE and PRRSV-positive cells were observed in type 2 infections. PRRSV mediator proteins, CD151, CD163, sialoadhesin (Sn), integrin and vimentin, were upregulated following type 1 and type 2 infection. CD151, CD163 and Sn were upregulated by type 2. In both PRRSV types, mRNA expression of TLR1 and TLR6 was upregulated. However, TLR3 was upregulated by type 1, but TLR4 and TLR8 mRNA and protein were downregulated by type 2 only. Interleukin (IL)-1β, IL-6 and tumor necrotic factor (TNF)-α were upregulated by type 2, but IL-8 was upregulated by type 1. Both PRRSV type 1 and 2 stimulated IL-6 but suppressed TNF-α secretion. In addition, IL-1β secretion was suppressed only by type 2. These findings reveal an important mechanism underlying the strategy of PRRSV infection in the endometrium and associated with the viral persistence.